Partisipasi Bank Indonesia Dalam Pengaturan Digitalisasi Sistem Pembayaran Indonesia - Rini Puji Astuti; Nabila Syahda Kamila; Nurul Holida; Muzayyanah Agustin (CV. ITTC INDONESIA, 2024)
The payment system as one part of financial infrastructure relating to funds transfer has made a large contribution in accelerating and expanding financial inclusion as the national financial inclusion strategy implementation. The payment system fluency guarantee is an inexorable necessity in the digital technology development era. This is both a responsibility and challenge for Bank Indonesia. The research purposes are to understand and analyze the regulation of Indonesia payment system by Bank Indonesia in the digital technology development era. The research uses normative juridical approach through library studies from various legal material sources. The regulation of Indonesia payment system by Bank Indonesia in the digital technology development era is held with reference to the five visions of Indonesia Payment System 2025 in IPS Blueprint 2025.